Greenhouse gas emissions from passive composting of manure and digestate with crop residues and biochar on small-scale livestock farms in Vietnam - Vu, Quynh Duong; Neergaard, Andreas de; Tran, TD; Hoang, HTT; Vu, VTK; Jensen, Lars Stoumann (Informa UK Limited, 2015)
This study investigated the effects of different mixing ratios of crop residues and biochar with liquid digestate from anaerobically treated pig manure on CH4, CO2, and N2O emissions over 84 days in a system of passive aeration composting, resembling typical Vietnamese solid manure storage conditions. Two treatments with solid manure were included for comparison. The results showed that C losses through CH4 and CO2 emissions accounted for 0.06–0.28% and 1.9–26.7%, respectively, of initial total C. CH4 losses accounted for just 0.4–4.0% of total C losses. Total N losses accounted for 27.1–40% of initial total N in which N2O emissions corresponded to 0.01–0.57% of initial total N, and hence accounted for only 0.1–1.8% of total N losses. It is assumed that the remainder was either the result of denitrification losses to N2 or ammonia volatilization. The composting of biochar (B) or crop residue with digestate (D) showed significantly lower CH4 and N2O emissions compared with composting manure (M) (p < .05). The composting of digestate with biochar showed significantly lower CO2 and CH4 emissions and significantly higher N2O emissions compared to the composting of digestate with rice straw (RS) (p < .05). The combined composting of digestate with biochar and rice straw (D + B + RS5:0.3:1) showed significantly reduced N2O emissions compared with composting digestate with biochar with alone (p < .05). Composting sugar cane bagasse (SC) with digestate (D + SC) significantly reduced CH4 and N2O emissions compared with the composting of rice straw with digestate (D + RS3.5:1 and D + RS5:1) (p < .05).